A Coverless Information Hiding Algorithm Based on Grayscale Gradient Co-occurrence Matrix. (25th December 2018) - Wu, Jianbin; Liu, Yiwen; Dai, Zhenwei; Kang, Ziyang; Rahbar, Saman; Jia, Yanke
ABSTRACT: In this paper, a coverless information hiding algorithm is introduced. In which, the grayscale gradient co-occurrence matrix is used to encode images and the mapping relationship between the images and the random numbers is used to express the payload information. There are three steps for this algorithm. Firstly, the grayscale gradient co-occurrence matrix of cover image is calculated, in accordance with which a descriptor is introduced. Secondly, the descriptor is quantized into a binary sequence to construct a mapping relationship between the cover image and the binary random numbers. Finally, the binary secret information sequence is divided into many segments, and the correct images corresponding to those segments are selected from the image database according to the mapping relationship. Moreover, the secret information is encrypted by Turbo encoder to improve the security. The experimental results show that the proposed algorithm has a good tolerance towards JPEG compression attack and low-pass filter attack. This promising algorithm which can be applied into remote sensing satellites leads an applied value in covert communication with high-security.